2011
DOI: 10.1519/jsc.0b013e3181cc22cc
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Postmatch Fatigue in Professional Rugby League Players

Abstract: The aim of the present study was to identify neuromuscular, biochemical, and endocrine markers of fatigue after Rugby League match play. Seventeen elite Rugby League players were monitored for a single match. Peak rate of force development (PRFD), peak power (PP), and peak force (PF) were measured during a countermovement jump (CMJ) on a force plate pre and postmatch play. Saliva and blood samples were collected 24 hours prematch, 30 minutes prematch, 30 minutes postmatch, and then at 24-hour intervals for a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
169
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(192 citation statements)
references
References 30 publications
13
169
1
3
Order By: Relevance
“…It would seem that cortisol works in two ways: for mental tasks, the demand for cortisol is high but recruitment of brain regions is lower than for physical tasks where the demands on cortisol levels are lower, consistent with elite athletes where cortisol activity is lowered with more training and possibly, more brain regions are recruited with an increase in skills set [34][35][36]. Averaging brain scan results across participants revealed that overall, recruitment of brain region activity is slightly greater than in the physical condition.…”
mentioning
confidence: 86%
“…It would seem that cortisol works in two ways: for mental tasks, the demand for cortisol is high but recruitment of brain regions is lower than for physical tasks where the demands on cortisol levels are lower, consistent with elite athletes where cortisol activity is lowered with more training and possibly, more brain regions are recruited with an increase in skills set [34][35][36]. Averaging brain scan results across participants revealed that overall, recruitment of brain region activity is slightly greater than in the physical condition.…”
mentioning
confidence: 86%
“…Monitoring training loads is necessary since the balance between training load and recovery is a determinant factor to obtain positive adaptations to training 9 . Studies have shown a decline in countermovement vertical jump (CMJ) performance after basketball training sessions 10 , after cumulative sessions of overload rugby training with limited recovery 11 , after a rugby game 12 , and after a period of rugby competitions 13 . The loss of muscle function observed after these exhaustive exercises is related to metabolic fatigue and the magnitude of exercise-induced muscle injury 7,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Measures of neuromuscular function have commonly been used to examine the fatigue response following team sport activities and have been suggested to be reliable indicators of low-frequency fatigue [7,8]. Neuromuscular function has been assessed using jumping protocols, sprinting performance, and isokinetic and isointertial dynamometry.…”
mentioning
confidence: 99%
“…Blood and salivary markers have been used to examine the possible mechanisms associated with neuromuscular and perceptual fatigue following team sport competition [7,14,16]. Although testing samples can be expensive, changes in biochemical, hormonal and immunological measures can be easily assessed around daily training activities with non-invasive blood capillary samples and salivary swabs.…”
mentioning
confidence: 99%
See 1 more Smart Citation